The role of mitochondria in inflammatory syndromes - Vanasco, Virginia (2016)
Several authors have addressed the importance of mitochondrial function in inflammatory syndromes,as it may play a role in the genesis of tissue injury. Sepsis and exposition to environmental particles are examples of inflammatory conditions. Sepsis occurs with an exacerbated inflammatory response that damagestissue mitochondria and impairs bioenergetic processes. One of the current hypotheses for the molecular mechanisms underlying the complex condition of sepsis is that enhanced NO production and oxidative stress lead to mitochondrial dysfunction, bioenergetic derangement and organ failure. The mechanism of particulate matter-health effects are believed to involve inflammation and oxidative stress. Components in particles that elicit inflammation have been poorly investigated, although recent research points out to the contribution of compositional elements and particle size. Oxygen metabolism and mitochondrial function appear to be important areas of study in inflammatory conditions for clarifying molecular mechanisms involved.